A TRANSLATION ANALYSIS OF CONJUNCTION ON NOVEL: INSIDE THE KINGDOM BY CARMEN BIN LADEN AND ITS TRANSLATION - HARTANTI , ARI WIDI (2011)
This research studies about the translation analysis of conjunction in Inside the Kingdom into Di dalam Kerajaan. The objectives of the study are to classify the types of conjunction found on Inside the Kingdom dan Di dalam Kerajaan and to describe the translation equivalence of conjunction translation in Inside the Kingdom and their translation. This research is a descriptive qualitative research. The objects of the research are conjunctions found in Inside the Kingdom and it's translation Di Dalam Kerajaan. The data are in the forms of conjunctions used in phrases, clauses, and sentences. They are collected from both the books by using document method. She applies comparison method in analyzing the data of the study. The results of data analysis show that firstly, there are two types of conjunction, namely: coordinate and subordinate conjunction. These conjunctions are then classified based on their uses in phrases, clauses, and sentences as cumulative, adversative, illative, disjunctive, cause/reason, comparison, condition, adversative, time, and purpose. From 112 data found, there are 64 data or 57.14% of coordinate conjunction and 48 data or 42.86% of subordinate conjunction. The coordinate conjunction consists of 30 conjunctions as cumulative, 17 conjunctions as adversative, 3 conjunctions as disjunctive, 14 conjunctions as illative. The subordinate conjunction consists 8 conjunctions as cause / reason, 3 conjunctions as comparison, 4 conjunctions as adversative, 11 conjunctions as condition, 12 conjunctions as time, and 10 conjunctions as purpose. Secondly, the equivalence of translation is divided into equivalent translation and non equivalent translation. The translations are dominated with equivalent translation. From 112 data, there are 95 data or 84.82% belong to equivalent translation and only 17 data or 15.18% fit in non equivalent translation.